Root Endophytism by Pochonia chlamydosporia Affects Defense-Gene Expression in Leaves of Monocot and Dicot Hosts under Multiple Biotic Interactions - Tolba, Shimaa R. T. (Plants (Basel), 2021)
A study was carried out on the effect of the root endophytic fungus Pochonia chlamydosporia on plant systemic signal of defense related genes during fungal or nematode parasitism. Different biotic stress factors were examined, inoculating roots of dicot and monocot hosts with the endophyte, and measuring the expression of defense genes in leaves. A first greenhouse assay was carried out on expression of PAL, PIN II, PR1 and LOX D in leaves of tomato cv Tondino inoculated with Phytophthora infestans (CBS 120920), inoculating or not the roots of infected plants with P. chlamydosporia DSM 26985. In a second assay, plants of banana (Musa acuminata cv Grand Naine) were artificially infected with Fusarium oxysporum f. sp. cubense Tropical race 4 (TR4) and inoculated or not with DSM 26985. In a further experiment, banana plants were inoculated or not with P. chlamydosporia plus juveniles of the root knot nematode (RKN) Meloidogyne incognita. A similar assay was also carried out in vitro with adults and juveniles of the lesion nematode Pratylenchus goodeyi. Differential expression of the defense genes examined was observed for all plant-stress associations, indicative of early, upward systemic signals induced by the endophyte. Changes in expression profiles included a 5-fold down-regulation of PIN II at 2 dai in leaves of tomato plants treated with P. infestans and/or P. chlamydosporia, and the up-regulation of PAL by the endophyte alone, at 2 and 7 dai. In the TR4 assay, PR1 was significantly up-regulated at 7 dai in banana leaves, but only in the P. chlamydosporia treated plants. At 10 dai, PIN II expression was significantly higher in leaves of plants inoculated only with TR4. The banana-RKN assay showed a PR1 expression significantly higher than controls at 4 and 7 dai in plants inoculated with P. chlamydosporia alone, and a down-regulation at 4 dai in leaves of plants also inoculated with RKN, with a PR1 differential up-regulation at 10 dai. Pratylenchus goodeyi down-regulated PIN at 21 dai, with or without the endophyte, as well as PAL but only in presence of P. chlamydosporia. When inoculated alone, the endophyte up-regulated PR1 and LOX. The gene expression patterns observed in leaves suggest specific and time-dependent relationships linking host plants and P. chlamydosporia in presence of biotic stress factors, functional to a systemic, although complex, activation of defense genes.